Development of an anthropomorphic robotic hand with tactile perception - Santos, Artur Vitório Andrade (2019)
In this paper the development of an anthropomorphic robotic hand with tactile perception is presented through the methodology of product development, developing kinematic calculations and performing manipulation on objects to validate a proposed solution. The robotic hand has 15 degrees of freedom, with the active compliance control system, developed through Raspberry Pi. Of 15 specifications proposed, only 5 were not satisfactorily attended.